The image of China and Chinese urban geography in the Western World: Reflections from the Iberian Peninsula - Lois González, Rubén Camilo; Piñeira Mantiñán, María José (Documents d’Anàlisi Geogràfica, 2017)
Following Edward Said, since the Middle Ages, Chinese civilization has appeared, to the eyes of Europeans, as a perfect example of the Oriental. This image evoked remoteness and a certain exoticism, and implied a lack of knowledge about the internal keys of this vast territory, except where Chineseness entailed novelty (gunpowder, clothing, pasta, etc.). This deeply rooted image in the West has been transferred to European and American science since the nineteenth century. This article verifies the enormous ignorance reflected in prestigious history and geographical theory books written in Spanish, French and English on the nation’s achievements. In our world, however, the tremendous potential exhibited by China over the last decades has aroused great interest. In this line, two recently published interpretative works by Gloria Davies and Gianni Arrighi about Chinese economic logic, culture and scientific behaviour are discussed. The field of geography and urban studies have also come to focus attention on these issues, as demonstrated in the growing number of works related to cities of China and the Chinese urbanization process in leading international journals on the subject.